2022
DOI: 10.3390/w14142267
|View full text |Cite
|
Sign up to set email alerts
|

Species Diversity, Distribution, and Abundance of Freshwater Snails in KwaZulu-Natal, South Africa

Abstract: Disease distribution is correlated to the distribution of the freshwater snails which in turn is influenced by the physicochemical status of the habitats. This study aimed to evaluate freshwater snail species diversity, abundance, and distribution in KwaZulu-Natal (KZN) province, South Africa, between December 2020 to February 2021. A total of 4576 freshwater snails consisting of 8 species were collected from 127 sites in 11 districts. Tarebia granifera snails were the most abundant (n = 2201), while bivalves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Although water velocity was not measured in this study, Bu. globosus snails are not found in water exceeding 0.3 m/s as they cannot attach themselves to the rocks [ 34 ]. Annual rainfall higher than 1192.2 mm leads to higher humidity, negatively impacting snail populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although water velocity was not measured in this study, Bu. globosus snails are not found in water exceeding 0.3 m/s as they cannot attach themselves to the rocks [ 34 ]. Annual rainfall higher than 1192.2 mm leads to higher humidity, negatively impacting snail populations.…”
Section: Discussionmentioning
confidence: 99%
“…Other freshwater snails such as Bulinus tropicus , Bulinus forskalii , Physa acuta , Tarebia granifera, and Bivalves, which are not intermediate host for human schistosomiasis have to a lesser extent been studied in KwaZulu-Natal compared to human schistosomiasis intermediate host snails: Bulinus globosus and Biomphalaria pfeifferi 7 . Previous studies have shown the effects of water physicochemical parameters such as water temperature, pH, dissolved oxygen, total dissolved solids, electrical conductivity, and climatic factors such as land surface temperature and rainfall on the distribution and abundance of freshwater snails 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study on the diversity, distribution and abundance of freshwater snails in all the districts in KZN province has also been carried out 7 . However, the study lacked information on temporal and seasonal patterns of freshwater snails in KZN as the study was cross-sectional based and accounted for the rainy season only.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown a positive correlation between other freshwater snails ( Tarebia granifera ) and Bulinus globosus [ 67 , 68 ] whereas a recent study showed a negative correlation, though not significant, between B . globosus and the invasive Physa acuta [ 69 ]. This finding has implication for further investigation as research has shown that P .…”
Section: Discussionmentioning
confidence: 99%